Gluconobacter Oxydans-Based MFC with PEDOT:PSS/Graphene/Nafion Bioanode for Wastewater Treatment - Tarasov, Sergei; Plekhanova, Yulia; Kashin, Vadim; Gotovtsev, Pavel; Signore, Maria; Francioso, Luca; Kolesov, Vladimir; Reshetilov, Anatoly (Biosensors (Basel), 2022)
Microbial fuel cells (MFCs) are a variety of bioelectrocatalytic devices that utilize the metabolism of microorganisms to generate electric energy from organic matter. This study investigates the possibility of using a novel PEDOT:PSS/graphene/Nafion composite in combination with acetic acid bacteria Gluconobacter oxydans to create a pure culture MFC capable of effective municipal wastewater treatment. The developed MFC was shown to maintain its activity for at least three weeks. The level of COD in municipal wastewater treatment was reduced by 32%; the generated power was up to 81 mW/m2 with a Coulomb efficiency of 40%. Combining the MFC with a DC/DC boost converter increased the voltage generated by two series-connected MFCs from 0.55 mV to 3.2 V. A maximum efficiency was achieved on day 8 of MFC operation and was maintained for a week; capacitors of 6800 µF capacity were fully charged in ~7 min. Thus, G. oxydans cells can become an important part of microbial consortia in MFCs used for treatment of wastewaters with reduced pH.